Co-expression of Cassia tora 1-deoxy-D-xylulose-5-phosphate synthase and 1-deoxy-D-xylulose-5-phosphate reductoisomerase enhances tolerance of transgenic Nicotiana benthamiana to lead (Pb) stress - Huang, Xue; Tian, Chunyao; Ma, Zichun; Chen, Jieru; Liu, Hongting; Zhang, Wei; Li, Zhongda; Lu, Pingping; Wang, Leyao; Liao, Hai; Zhou, Jiayu (Frontiers in Plant Science, 2025)
Lead (Pb) stress causes impairment of plant growth and loss in crops. Exogenous addition of abscisic acid (ABA) could alleviate Pb damage, however, the roles of genes involved in the biosynthesis of ABA in Pb tolerance were still unclear. In this study, we found that the transcription of Cassia tora 1-deoxy-D-xylulose-5-phosphate synthase 1 (CtDXS1) and 1-deoxy-D-xylulose-5-phosphate reductoisomerase 1 (CtDXR1) genes was upregulated by lead acetate (Pb). Subsequently, we evaluated the anti-Pb effects of Nicotiana benthamiana coexpressing CtDXS1 and CtDXR1 genes. The transgenic lines conferred improved performance under Pb stress, such as more endogenous ABA content and higher antioxidant enzyme activities, but lower levels of malonaldehyde (MDA) and H2O2 contents as well as Pb uptake than in the wild-type plants. Additionally, the role of ABA in Pb tolerance was verified. The transcript of heavy metal-tolerant genes, such as ABC transporters and ATPase, were enhanced in the transgenic plants, with auxin transporter protein 1 (AUX1) and calcium-binding protein CP1 (CP1) being potential key nodes in Pb-tolerant signaling network. In addition, Pb-tolerant microbes such as genera Methylophilus, Massilia and Bradyrhizobium were enriched in the rhizosphere microbial community of transgenic plants. To our knowledge, this first report demonstrating 2-C-methyl-D-erythritol-4-phosphate (MEP) pathway-mediated accumulation of ABA confers Pb tolerance.